2020
DOI: 10.1039/c9ta10990k
|View full text |Cite
|
Sign up to set email alerts
|

Ni–WSe2nanostructures as efficient catalysts for electrochemical hydrogen evolution reaction (HER) in acidic and alkaline media

Abstract: Doping WSe2 with various metals promotes the HER. Ni doping was found as the most efficient dopant, forming grafted layers on the structures. The mechanisms of the enhanced activity are unveiled and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 56 publications
8
84
0
Order By: Relevance
“…Water oxidation in the absence [1 M KOH] and presence [1 M KOH+0.33 M urea] of urea was conducted, and the polarization curves are given in Figures 3a and 4a, respectively. Similar to previously reported transition metal chalcogenides for water oxidation [10,13,35,36] . An initial electrochemical activation was observed under anodic treatment at 1.4 V vs. RHE, which is attributed to the Ni 2+/3+ transformation.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Water oxidation in the absence [1 M KOH] and presence [1 M KOH+0.33 M urea] of urea was conducted, and the polarization curves are given in Figures 3a and 4a, respectively. Similar to previously reported transition metal chalcogenides for water oxidation [10,13,35,36] . An initial electrochemical activation was observed under anodic treatment at 1.4 V vs. RHE, which is attributed to the Ni 2+/3+ transformation.…”
Section: Resultssupporting
confidence: 89%
“…As the polarization curves (Figure S9) indicate, MS‐NS showed the best performance, followed by FS@FO‐NS and NS, with all the electrodes exhibiting superior performance in alkaline electrolyte to acidic electrolyte. This phenomenon was observed in previous works dealing with Ni‐based electrodes for HER [36] . The increased performance in 1 M KOH is explained by the ability of Ni to facilitate water dissociation, which overcomes the rate‐determining step for HER in alkaline electrolyzers [37] .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…On the other hand, Seok et al [73] have reported the intrinsic activity for HER on MoTe 2 nanosheet via the first-principle calculation and scanning tunneling microscopy (STM) study. Besides, numerous researchers also successfully developed promising WS 2 -based and WSe 2 -based electrocatalysts recently (e.g., Te-WS 2 nanosheet by Pan et al [74]; and Ni-WSe 2 nanosheet by Kadam et al [75]).…”
Section: Adsorption Of Water Vapor (H 2 O)mentioning
confidence: 99%
“…Two‐dimensional layered transition metal dichalcogenides (TMDs) play an important role in catalysis due to their wide range of optical and electronic properties. The layered structure provides high surface area and low charge recombination characteristics, both desirable for the design of new catalysts . Among the various metal sulfides, SnS 2 is a naturally occurring bronze‐colored n‐type narrow band gap semiconductor .…”
Section: Introductionmentioning
confidence: 99%